FUNCTIONAL INDEPENDENCE OF THE PERSON WITH SPINAL INJURY: INJURY AT THE FIRST HOSPITALIZATION - Gelson Aguiar Da Silva Moser; Francine Lima Gelbcke; Denise Consuelo Moser Aguiar; Soraia Dornelles Schoeller; Fabiana Faleiros Santana Castro (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objective: To identify the perception of the person with spinal cord injury from the accident on trauma, rescue and urgent and emergency care. Methods: exploratory study, with a qualitative approach carried out with ten people with traumatic spinal cord injury between September and November 2014, residing in Chapecó-SC. For data collection, semi-structured interviews were used, and the data were submitted to Thematic Content Analysis. Results: Eight men and two women aged between 18 and 35 years were interviewed. Among the empirical categories that emerged from the process of apprehending the data are: the beginning of functional disability: trauma; and the rescue and urgent care (Emergency Room and Intensive Care Unit). Conclusion: The rehabilitation process of the person with spinal cord injury should be started as early as possible, which highlights the importance of pre-hospital care. It is up to the pre-hospital care team to intensify this care in order to assist in the conduct of functional independence.